Computational insights into β-site amyloid precursor protein enzyme 1 (BACE1) inhibition by tanshinones and salvianolic acids from Salvia miltiorrhiza via molecular docking simulations. (June 2018) - Yu, Ting; Paudel, Pradeep; Seong, Su Hui; Kim, Jeong Ah; Jung, Hyun Ah; Choi, Jae Sue
Graphical abstract: Highlights: Twelve tanshinones, three salvianolic acids and caffeic acid derivatives were evaluated for anti-Alzheimer's property. Deoxyneocryptotanshinone, salvianolic acid A and salvianolic acid C showed strong BACE1 inhibition. Enzyme kinetics and molecular docking simulations were performed for active compounds. Structure-activity relationship was discussed. Abstract: The rhizome of Salvia miltiorrhiza has emerged as a rich source of natural therapeutic agents, and its several compounds are supposed to exhibit favorable effects on Alzheimer's disease (AD). The present work investigate the anti-AD potentials of 12 tanshinones, three salvianolic acids and three caffeic acid derivatives from S. miltiorrhiza via the inhibition of β-site amyloid precursor protein cleaving enzyme 1 (BACE1). Among the tested compounds, deoxyneocryptotanshinone (1 ), salvianolic acid A (13 ) and salvianolic acid C (15 ) displayed good inhibitory effect on BACE1 with IC50 values of 11.53 ± 1.13, 13.01 ± 0.32 and 9.18 ± 0.03 μM, respectively. Besides this, enzyme kinetic analysis on BACE1 revealed 13, a competitive type inhibitor while 1 and 15 showed mixed-type inhibition. Furthermore, molecular docking simulation displayed negative binding energies (AutoDock 4.2.6 = −10.0 to −7.1 kcal/mol) of 1, 13, and 15 for BACE1, indicating these compounds bound tightly to the active site of the enzyme with low energy and high affinity. The results of the present study clearly demonstrate that S. miltiorrhiza and its constituents have potential anti-AD activity and can be used as a therapeutic agent for the treatment of AD.